A tailored direct-to-indirect band structure transition in double perovskite oxides influences its photocatalysis efficiency. Issue 5 (1st March 2023) - Halder, Saswata; Kumar, Ram Awdhesh; Maity, Ritwik; Sinha, T.P.
Abstract: The increase in cost-effective materials for harvesting solar energy is essential for the development of renewable energy technologies. Photovoltaics and photocatalysts are been actively researched in the field of harvesting solar photons. In this communication, we explore stable Ru-doped Ba2 HoSbO6 (BHSR) complex perovskites with promising photocatalytic properties and a bandgap that is tunable in the UV–Vis region. The band gap shows a non-linear decrease with increased Ru doping, which follows an asymmetrically-weighted Vegard's law. UV–Visible absorption measurements and density functional theory (DFT) based simulations reveal a transition in magnitude (energy) as well as nature of the band structure (direct-to-indirect) upon Ru substitution; an observation which is unique and can influence future band structure engineering in perovskite oxides. This tailored band structure engineering plays an important role in the carrier recombination process aptly captured through photoluminescence (PL) spectroscopy. The photocatalytic activity of BHSR is demonstrated through a time varying photo-degradation of rhodamine B (Rh–B)-particulate BHSR solution. The catalytic activity is seen to improve with increased Ru doping which can be attributed to the reduction in the electron localization (electrical conductivity), increased dielectric screening, decrease in band gap and carrier recombination (electronic structure).